Ethics and Literary Practice - Newton, Adam Zachary (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This volume draws together a diverse array of scholars from across the humanities to formulate and address the question of "ethics and literary practice" for a new decade. In taking up a conjunction whose terms remain productively open to question, fifteen essays survey a range of approaches and topics including genre and disciplinary rhetoric, emergence theory and literary signification, the ethics of alterity, of attention, and of aesthetics, the decolonial and the paracritical, neorealism and contingency, analogy and affect, scripture and national literature. From Seamus Heaney to Hannah Arendt, Teresa Brennan to Stanley Cavell, Ronit Matalon to Édouard Glissant, Uwe Timm to Katherena Vermette, Notes for Echo Lake to the Gospel of St. Matthew, these contributions demonstrate how broadly and fruitfully ramifying its organizing inquiry can be. Bringing such multifarious perspectives to the topic feels only more urgent as language, meaning, and expression enter the crucible of a "post-truth" era.